(untitled) (Canadian Journal of Counselling and Psychotherapy, 2017)
This fictional case study explores various components of person-centred therapy and transpersonal psychotherapy as applied to the conceptualization of a bulimia nervosa case study and psychotherapeutic treatment. The strengths and limitations of these theories in the conceptualization and treatment of bulimia nervosa are discussed.